'The ownership was based on club and stick': the cartographic reconstruction of a medieval monastic estate in the Buzău Region, Romania. (3rd July 2018) - Buterez, Cezar; Cepraga, Theodor
ABSTRACT: The dynamics of property regime play a key role in understanding the socio-economic and cultural evolution of the Romanian Principalities during the late Middle Ages. In the seventeenth and the eighteenth centuries the main landowners were the boyars (the local elite), the ecclesiastical institutions and the free peasants. The latter, known to have financial obligations only to the State, were in a constant feud with the boyars and the monasteries for the landownership of their estates. A rather common practice for the free peasants was to found a skete (a monastic community) and to endow it with a part of their domain. Focusing on the Buzău Subcarpathians, this paper attempts to examine the spatial dimensions of an estate donated by a free peasant, who later became a monk, to the skete founded by him. The paper uses the toponyms extracted from historical documents, oral histories and GIS to precisely locate the seventeenth-century estate and its subsequent evolution. The approach also serves as a tool for understanding the role played by the estates from a social, economic and administrative point of view. Finally, the paper explains the importance of the findings to the dynamic of the regional administrative county bounds, to the creation of a Historical-Geographical Information System (HGIS) in Romania and also to local tourism.